Effect of land use and organic matter on nitrogen and carbon labile fractions in a Typic Hapludult - Andy Wijanarko; Benito Heru Purwanto (Journal of Degraded and Mining Lands Management, 2017)
A study that was aimed to determine the effect of organic matter from groundnut and maize biomass on the availability of N and C labile fraction was conducted in laboratory and glasshouse, Iletry, Malang. Research used randomized block design with three replications. The first factor was land use : (1). Soil from land cultivated by cassava crops for less than 10 years, and (2). Soil from land cultivated by cassava crops for more than 30 years. The second factor was type of organic matter: (1). Groundnut biomass, (2). Maize biomass, (3). Groundnut-maize biomass, with a ratio of 1:1, (4). Groundnut – maize biomass, with a ratio of 2:1, (5). Groundnut – maize biomass, with a ratio of 1:2, and (6). Without organic matter. The results showed that application of groundnut and maize biomass were affect the N and C labile fraction. Application of groundnut + maize biomass increases N and C labile fraction more 40% than without biomass as well as the landuse of planted with cassava less than 10 years was 20 % higher N and C labile fractions than the land that has been planted with cassava more than 30 years. This research showed that analysis of N or C labile fraction is more sensitif than analysis of N total or C organic. It indicates that analysis of labile fractions can be used to analyze of N and C availability in the soil, beside of N total and C organic analysis